2020
DOI: 10.1007/s00277-020-04018-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between molecular response and quality of life with bosutinib or imatinib for chronic myeloid leukemia

Abstract: Patients with newly diagnosed chronic phase chronic myeloid leukemia (CP CML) can be effectively treated with tyrosine kinase inhibitors (TKIs) and achieve a lifespan similar to the general population. The success of TKIs, however, requires long-term and sometimes lifelong treatment; thus, patient-assessed health-related quality of life (HRQoL) has become an increasingly important parameter for treatment selection. Bosutinib is a TKI approved for CP CML in newly diagnosed adults and in those resistant or intol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Changes from baseline in patient-reported outcomes measures at month 12 were comparable to those observed in previously treated patients in the initial phase 1/2 study of bosutinib, wherein long-term efficacy and HRQoL stability were reported [ 19 , 37 , 38 ]. In addition, FACT-G scores in the current study were consistent with those previously reported for bosutinib in newly diagnosed patients with CML, in the general population, as well as in patients with various cancers [ 39 – 43 ]. Maintenance of HRQoL is important for patients with CP CML who potentially will receive lifelong TKI treatment, and PRO results from this phase 4 study suggest bosutinib is a treatment option with manageable AEs, providing further support for its use in patients with CP CML resistant/intolerant to prior TKIs.…”
Section: Discussionsupporting
confidence: 91%
“…Changes from baseline in patient-reported outcomes measures at month 12 were comparable to those observed in previously treated patients in the initial phase 1/2 study of bosutinib, wherein long-term efficacy and HRQoL stability were reported [ 19 , 37 , 38 ]. In addition, FACT-G scores in the current study were consistent with those previously reported for bosutinib in newly diagnosed patients with CML, in the general population, as well as in patients with various cancers [ 39 – 43 ]. Maintenance of HRQoL is important for patients with CP CML who potentially will receive lifelong TKI treatment, and PRO results from this phase 4 study suggest bosutinib is a treatment option with manageable AEs, providing further support for its use in patients with CP CML resistant/intolerant to prior TKIs.…”
Section: Discussionsupporting
confidence: 91%
“…A previous analysis of BFORE demonstrated that HRQoL was maintained or improved compared with baseline after 12 months of bosutinib or imatinib treatment [ 17 ]. In addition, a pooled analysis of the bosutinib and imatinib arms showed that a better molecular response with tyrosine kinase inhibitor treatment was generally associated with improved HRQoL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…BFORE (ClincalTrials.gov, NCT02130557) was an open-label, randomized, multicenter, phase 3 study; methods have been published [ 7 , 8 ]. Patients aged ≥18 years, with newly diagnosed BCR::ABL1 -positive CP CML, were randomized 1:1 to receive (starting dose) bosutinib or imatinib 400 mg once daily.…”
Section: Methodsmentioning
confidence: 99%
“…However, while there exist substantial comparative data on the efficacy and safety of newer TKIs in the hematology field, little is known regarding HRQoL as perceived by patients with CML treated with TKIs [61]. As stated by Brümmendorf et al [43], the associations between the efficacy of treatment for CML by TKIs and HRQoL are largely unknown. In the present systematic review, out of the included seven, just two RCTs [45,47] selected HRQoL as the primary outcome, and the other two considered it as a primary outcome in association with molecular response to the TKIs therapy [40] or in a post-hoc analysis [44], after considering other clinical outcomes from the original ENEST trial [62].…”
Section: Discussionmentioning
confidence: 99%
“…The study carried out by Brümmendorf et al [43], as well as that of Cortes et al [42] just described above, regard findings from BFORE trial [41], a multicenter study primarily aimed to assess the efficacy and safety of bosutinib versus imatinib for first-line treatment of chronic-phase CML. Brümmendorf et al [43] examined the relationships between molecular response (MR) and HRQoL after imatinib or bosutinib treatments. They represented MR values by a Log Reduction scale (MRLR), in order to consider the MRLR as a continuous variable.…”
Section: Findings By the Included Rcts With Respect To Hrqolmentioning
confidence: 99%